Transformation of [60] Fullerene to a Derivative C120O by Shock-Compression - Hong-Chang, Z.; Ru-Fang, P.; Bo, J.; Hua, L.; Bi-Sheng, T.; Shi-Jin, C. (Asian Journal of Chemistry, 2012)
For study on the transformed behaviour of C60 under the high temperature and pressure, C60 fullerene powder was impacted by shock wave at 14.3 gigapascals, generated by a high-speed flyer, in helium. For toluene extraction, the mixtures were isolated using high performance liquid chromatography. The targets, which were obtained from mixtures, were examined with Mass spectrum and other methods. The results showed that most of the C60 were decomposed, a small part transformed to C120O and other carbon cluster under the shock wave. The C60 powder transformed to dimeric fullerene oxide C120O were also discussed.